Study Of Entomopathogenic Nematodes History (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Entomopathogen nematodes Uzbekistan fauna for yet not studied species this is for the first time in the article of Uzbekistan potatoes from agrobiocenoses separate received entomopathogenic of nematodes morpho-biological features the world scientists in experience to be studied ie entomopathogenic of nematodes study history about analytical data present will be done